S77 Comparing the degree of inhibition of TNF-α and IL-6 by p38 inhibitors in monocyte derived macrophages (MDMs). (2nd December 2011) - Noble, R A; Patel, S; Kilty, I
Abstract : Objective: The activation of p38 MAPK is involved in the increased expression of pro-inflammatory cytokines, such as TNF-α and IL-6, in inflammatory diseases such as chronic obstructive pulmonary disease (COPD). Inhibition of p38 may therefore represent an effective means to combat inflammatory diseases. Inhibitors of p38 such as BIRB796 cause a rapid reduction in the levels of inflammatory cytokines. The aim was to assess the effect of three p38 inhibitors on the lipopolysaccharide (LPS) induced expression of cytokines; TNF-α IL-6 and IL-10 in MDMs. Methods: Peripheral blood mononuclear cells (PBMCs) were isolated from human peripheral blood taken from healthy human donors. Monocytes were subsequently selected through magnetic bead separation. Following the isolation of monocytes, cells were differentiated to MDMs over 12 days in suspension. BIRB796 and two novel p38 inhibitors, PH797804 and PF03715455 were pre-incubated for 1 h before stimulation with 100 ng/ml LPS. Supernatants were collected after 18 h and the levels of TNF-α IL-6 and IL-10 were determined by ELISA. The effects of the compounds were also assessed over 24 h. Supernatants were collected at several time-points allowing the onset and duration of the inhibitory effect to be observed. Results: BIRB796, PHA797804 and PF03715455 caused a substantial inhibition in the release of TNF-α (n=3) and IL-6 (n=3) in LPS-stimulated MDMs. The maximum level of inhibition ranged from 50% to 65%. The addition of the anti-inflammatory cytokine, IL-10, enhanced both the maximum level of inhibition and the potency of each compound. Cytokine expression across 24 h showed a dose dependant inhibition of cytokine release = 2 h (TNF-α) and =4 h (IL-6). The IC50 values in respect to both TNF-α and IL-6 decreased over time. Conclusion: The method described here is an effective means of comparing the effect of p38 inhibitors in MDMs. All three compounds caused a substantial inhibition of, LPS-stimulated, production of both TNF-α and IL-6. The effect of these compounds on IL-10 production requires further investigation. Since a reduction of the anti-inflammatory cytokine IL-10 may counteract the benefits that may be associated with reduced levels inflammatory cytokines due to p38 inhibition in inflammatory diseases.